Hepato-protective Potential of Hull Fraction from Indian Flaxseed Cultivar - Rajesha, J; Rao, A Ranga; Kumar, M Karuna; Ravishankar, GA (Asian Journal of Medical Sciences, 2011)
Objective: Secoisolariciresinol diglucoside (SDG) isolated from hull fraction of Indian flaxseed cultivar was studied for its hepatoprotective potential by measuring the level of hepatic enzymes such as catalase, peroxidase and superoxide desmutase (SOD) upon feeding to albino rats. Material & Methods: The animals were grouped into five groups (n=5): The first group served as normal and received normal diet without treatment of toxin and hull fraction of flaxseed. The second group was named the control and received a regular commercial diet. The third, fourth and fifth groups were fed with normal diet and supplemented with hull fraction of flaxseed (150 and 250 μg/kg) and standard SDG (150 μg/kg), that was mixed with olive oil for 14 days. Results: Pretreatment of rats with 150 μg/kg b.w hull fraction of flaxseed followed by CCl4 treatment caused restoration of catalase, SOD and peroxidase by 37.70%, 108.22% and 23.89% respectively as compared to control. The group treated with 250 μg/kg b.w hull fraction of flaxseed showed the restoration of 67.30%, 152.82% and 39.88% of catalase, SOD and peroxidase, respectively. Conclusion: In conclusion, SDG fed in the form of flaxseed hull is responsible for its hepatoprotective properties. Further, it can be used as a potential source of nutraceutical agent and studies are required in this field to examine its use in large scale for food and feed industries. Keywords: Flaxseed; hull fraction; SDG; antioxidant enzymes DOI: 10.3126/ajms.v1i2.2938 Asian Journal of Medical Sciences 1 (2010) 20-25